Inhibition of chromium poisoning in La0·6Sr0·4Co0·2Fe0·8O3-δ cathode via simple electroless silver plating for solid oxide fuel cells. (8th March 2022) - Wang, Zhenwei; Zhao, Shikai; Guo, Xue; Li, Jiao; Hu, Qiangqiang; Feng, Yurun; Yu, Fangyong; Sun, Haibin
Abstract: La0·6 Sr0·4 Co0·2 Fe0·8 O3-δ (LSCF), one kind of state-of-art solid oxide fuel cells (SOFCs) cathodes, often suffers from the chromium poisoning in the operating condition with Cr-based stainless steel interconnects, resulting in deteriorating cell performances. A simple electroless silver plating method was used to modify the surface of LSCF cathodes (named LSCF-Ag), and the anti-chromium stability of LSCF cathodes was studied. After the Cr treatment for 40 h, the polarization resistance ( R p ) of LSCF cathodes changes from 0.26 Ω cm 2 to 0.62 Ω cm 2 at 700 °C, while that of LSCF-Ag cathodes shows nearly no change (from 0.24 Ω cm 2 to 0.26 Ω cm 2 at 700 °C). In LSCF-Ag cathodes, the formation of AgCrO2 instead of SrCrO4 avoids the lack of excessive Sr in the A site of LSCF, and AgCrO2 has an electronic conductivity two orders of magnitude greater than SrCrO4, thereby exhibiting significant survivability to Cr. The single cell with LSCF-Ag cathodes after Cr treatment shows a stable peak powder density of 288 mW cm −2 at 700 °C while taking wet hydrogen and air as fuel and oxidizer. As a comparison, the peak power density of single cells with blank LSCF cathodes drops by 12%. It is suggested that the simple electroless silver plating on LSCF cathodes is an effective method to suppress cathode chromium poisoning. Graphical abstract: Image 1 Highlights: Ag modified LSCF cathodes are synthesized by the simple electroless plating. Ag loaded on the LSCF cathode can preferentially react with Cr to form AgCrO2 . Ag modified LSCF cathodes show excellent resistance and stability to chromium.